HUMAN RESOURCE MANAGEMENT MEETS PUBLIC POLICY: GII, EDUCATION PARITY, AND WOMEN’S LABOUR-FORCE PARTICIPATION - Adrianus Hondro; Titik Rosnani; Sulistiowati (Jurnal Ekonomi dan Manajemen, 2025)
Persistent gender gaps in labour-force participation (LFPR) constrain productivity and inclusive growth across East Asia and the Pacific (EAP). While many factors shape women’s economic engagement, structural gender inequality and disparities in human capital are consistently cited as key explanations. This study examines whether cross-country variation in the LFPR gap (male minus female, percentage-point difference) is associated with (i) the Gender Inequality Index (GII) and (ii) the male–female gap in secondary-education attainment. We conduct a cross-sectional, country-level analysis using secondary data from the United Nations Development Programme’s Human Development Report Statistical Annex (reference year 2023). Ordinary Least Squares (OLS) is estimated with heteroskedasticity-robust (HC3) inference. Robustness checks include institutional and health covariates—women’s representation in parliament, adolescent birth rate, and maternal mortality. Multicollinearity diagnostics (variance inflation factors) indicate low collinearity among regressors. Descriptive patterns show that countries with higher GII values and wider secondary-education gaps tend to exhibit larger LFPR gaps. In multivariate models, higher GII is positively and statistically associated with wider LFPR gaps. The secondary-education gap is positively related to the LFPR gap, though its magnitude and significance attenuate when institutional and health controls are included. Results remain directionally stable across specifications. Reducing gendered participation penalties in the EAP likely requires a dual strategy: expanding women’s secondary-education completion and strengthening enabling institutions (e.g., anti-discrimination enforcement, childcare and care infrastructure, safe and flexible work arrangements). Future work using panel or microdata is warranted to assess dynamics and mechanisms more precisely.